POTENSI EKSTRAK ETIL ASETAT Coprinus comatus TERHADAP KADAR SGOT DAN SGPT PADA TIKUS PUTIH MODEL DIABETES - Feryawan Feryawan; Nuniek Ina Ratnaningtyas; Nuraeni Ekowati (Fakultas Biologi Universitas Jenderal Soedirman, 2022)
Coprinus comatus or shaggy in cap mushroom contain bioactive compounds including flavonoids, alkaloids, terpenoids, tocopherols, comatin, and ergotionin which function as antioxidants and antidiabetic. Diabetes mellitus is a chronic disease associated with impaired insulin secretion or decreased insulin sensitivity which causes blood glucose levels to rise above normal (hyperglycemia). Hyperglycemia conditions can causes oxidative stress and increase Reactive Oxygen Species (ROS), to trigger lipid peroxidation which damages the pancreas, kidneys and liver. One way to determine liver damage is by measuring the increase in liver enzyme levels of Serum Glutamate Oxaloacetate Transaminase (SGOT) and Serum Glutamate Pyruvate Transaminase (SGPT) in the bloods. The aims in this study is determine the effect of administration and determine the effective doses of ethyl acetate C. comatus extract with different doses on the levels of SGOT and SGPT in the bloods of diabetic rats. The results showed that C. comatus ethyl acetate extract could reduce SGOT and SGPT levels as well as streptozotocin-induced rat bloods glucose levels. Ethyl acetate C. comatus extract with doses 500 mg / kg BW is the most effective doses in reducing SGOT and SGPT levels in the bloods of streptozotocin-induced rats with a mean SGOT level of 57,96 ± 1,58 U/L and SGPT levels of 29,67 ± 3,56 U/L, and the percentage reduction in SGOT and SGPT levels compared to negative controls respectively was 43,15% and 68,70%, and blood glucose was 19,62%.